ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP KEMAMPUAN ZAKAT PADA BANK SYARIAH (Studi Kasus Pada Bank Syariah Tahun 2012-2015) - Siti Masula; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis research aims to determine the effect of the financial performance ofthe ability of zakat. Population in this research were syariah banking companywhich listed in Bank Indonesia (BI) period 2012-2015. The sample in thisresearch were fiveteen companies using purposive sampling method. The analysisusing multiplelinear regression analysis technique, quality data test, andhypothesis test. Data processing use IBM SPSS (Statistical Product and ServiceSolution) program, Statistic 24 version. The results in this research showed thatfinancial performance (ROE, CR and DER) to effect of the ability of zakat. Theresults of regression showed that Adjusted R Square of 0,227, the meant the effectindependent variable of dependent variable was 22,7% and 77,3% was effect byother variables that not included in the this research.Key Words—Financial Performance, Zakat, ROE, CR, DER